SARS-CоV-2 spread in humans and animals - T. P. Akimiva; V. P. Semakina; M. N. Mitrofanova; M. V. Zhiltsova; E. S. Vystavkina; D. G. Isakova; D. B. Andreychuk; A. K. Karaulov; I. A. Chvala; A. E. Metlin (Ветеринария сегодня)
Coronaviruses are a large family of viruses and they are wide spread in animals and humans. They can cause respiratory tract illnesses of various severity. The latest recently discovered coronavirus (SARS-CoV-2) is an agent ofCOVID-19. The first human cases were reported in Wuhan (People’s Republic of China) in December2019. Since then, the disease infected over 153 million people and became the cause of more than 3 million deaths all over the world. Among the leaders in the confirmed cases are the USA, India, Brazil, France, Turkey and Russia. In February 2020, it was determined that some animal species, including domestic cats and dogs, can be infected with SARS-CоV-2. Reports of animal infection in zoos were submitted from the USA, Argentina, Czech Republic, Sweden, Spain, Estonia, RSA and India. Cases of SARS-CoV-2 infection in fur-farmed minks were reported by 13countries. The most large-scale COVID-19 outbreak in minks that involved about 300 mink farms was reported in Denmark. During the COVID-19 pandemic, the agent’s transmission from humans to canines (Canidae), felines (Felidae), mustelids (Mustelidae) and hominids (Hominidae) was confirmed. As of early May2021, the disease cases in animals were reported by 33countries. Due to COVID-19 epidemic spread and detection of animal infection cases, diagnosis tools and methods were developed in the Russian Federation, and screening tests were performed in susceptible animal populations in different regions of the country. COVID-19 monitoring results demonstrated the virus in two cats (in Moscow and Tyumen).